Entrepreneurs vs. Business Plans: A Study of Practicality and Usefulness - Anantadjaya, Sam PD (UI Scholars Hub, 2007)
In higher education, the topic on business plan is relatively studied in great details to note the importance on formulating business plans. Business plans are regarded as the reference point for business people; managers and members of the board of directors, to really realize the business activities. At least, the topic on business plan, which are discussed and studied in universities, ought to have its own value in the real business operations. Many entrepreneurs, however, face difficulties in formulating structural business plans. Many entrepreneurs may not actually formulate business plans as they are regarded important in many classrooms’ teaching, to provide necessary guidance toward corporate governance, opening up new business units, venture agreements, and/or expansion of business operations. Universities should provide connections between what is discussed in classrooms, and the implementation of such discussions in business practices. This research is intended to seek out relationships between the importance of structural business plans, and the practicality and usefulness of business plans for entrepreneurs in young organizations. The reference point for this research is business portfolio theory, both for individual and organization rational theory. One of such means discussed in this paper is the formulation and development of business plans to attract external funding in supporting the needs toward growth.